Differing, multiscale landscape effects on genetic diversity and differentiation in eastern chipmunks - Kierepka, Elizabeth M. (Heredity (Edinb), 2020)
Understanding how habitat loss and fragmentation impact genetic variation is a major goal in landscape genetics, but to date, most studies have focused solely on the correlation between intervening matrix and genetic differentiation at a single spatial scale. Several caveats exist in these study designs, among them is the inability to include measures of genetic diversity in addition to differentiation. Both genetic metrics help predict population persistence, but are expected to function at differing spatial scales, which requires a multiscale investigation. In this study, we sampled two distinct spatial scales in 31 independent landscapes along a gradient of landscape context (i.e., forest amount, configuration, and types of intervening matrix) to investigate how landscape heterogeneity influences genetic diversity and differentiation in the forest-associated eastern chipmunk (Tamias striatus). Overall, quality of intervening matrix was correlated with genetic differentiation at multiple spatial scales, whereas only configuration was associated with regional scale genetic diversity. Habitat amount, in contrast, did not influence genetic differentiation or diversity at either spatial scale. Based on our findings, landscape effects on genetic variation appears to differ based on spatial scale, the type of genetic response variable, and random variation among landscapes, making extrapolation of results from single scale, unreplicated studies difficult. We encourage landscape geneticists to utilize multiscale, replicated landscapes with both genetic diversity, and differentiation to gain a more comprehensive understanding of how habitat loss and fragmentation influence genetic variation.